Using temperament-based approaches to negotiate the terrains of crisis in Jamaican early childhood classrooms. Issue 3 (2nd July 2020) - Kinkead-Clark, Zoyah
ABSTRACT: One factor that put Jamaican children at risk is their exposure to everyday crisis which is defined as an existence where citizens are forced to live in harsh environments resulting from social issues including; crime, violence, economic depression, and social injustice. Guided by the findings which note children's perspectives of schools as violent and aggressive largely caused by teachers' dependence on harsh discipline, this study sought to examine teachers' perceptions of the use of temperament-based approaches to classroom management. Coupled with this, it also sought to glean how teachers perceived children felt about using temperament-based approaches to solve conflict with each other. Using thematic analysis to extricate the findings generated from a focus group discussion comprised of early years teachers, findings highlight that though not wholly successful, teachers appreciate the use of an alternative approach to harsh discipline. Likewise, teachers also felt children benefited from its use when solving conflict with others. Teachers noted limited understanding of the individuality of children's temperament fueled the use of harsh discipline. These findings have implications for teacher education and how teachers are prepared to deal with the realities of the Jamaican early childhood classroom.